Pharmacodynamic and Safety Results of PEG-Hirudin in Healthy Volunteers - Esslinger, Hans-Ulrich; Haas, Sylvia; Maurer, Robert; Lassmann, Axel; Dübbers, Katrin; Müller-Peltzer, Herbert (Thrombosis and Haemostasis, 1997)
PEG-Hirudin, a chemically defined conjugate of recombinant hirudin and two molecules of polyethylene glycol (PEG)-5000 is a highly selective direct thrombin inhibitor with a significantly longer duration of action than non-conjugated recombinant hirudin permitting once daily subcutaneous administration. A series of placebo-controlled, randomized, Phase I clinical trials were conducted in 75 healthy volunteers to investigate the anticoagulant effects, safety and pharmacodynamics of PEG-Hirudin when administered intravenously as a bolus injection, infusion, and subcutaneously. After single i.v. injections of various doses of PEG-Hirudin (0.03-0.3 mg/kg) dose-dependent increases in anti-IIa activity and APTT were observed. Four hours after injection of 0.3 mg/kg, mean plasma concentration expressed in terms of anti-IIa activity was still 0.89 µg/ml, corresponding to a 1.8-fold prolongation of APTT. Continuous intravenous infusions of 0.01 and 0.02 mg/kg/h PEG-Hirudin resulted in maximum anti-IIa activities of 0.42 µg/ml and 0.77 µg/ml, respectively, at the end of a six-hour infusion period without having reached steady state at this time. After termination of the infusion, anticoagulant activity displayed an immediate exponential decrease. The anticoagulant activities of single subcutaneous doses of 0.05 to 0.6 mg/kg were studied in a further series of investigations and slow increases and prolonged durations of anti-IIa activity and APTT prolongation were found. Repeated, once daily subcutaneous administrations of 0.2 to 0.4 mg/kg for five days resulted in dose-dependent prolongations of APTT and increases in anti-IIa activity without completely reaching steady state conditions. In a further study, 0.3 mg/kg of PEG-Hirudin was given as an i.v. bolus injection followed by three repeated single daily s.c. injections. In this trial, the APTT was shorter than expected from previous studies; therefore, a direct comparison of various APTT reagents was made in the intravenous infusion trial. Of the APTT reagents tested, BioMérieux Silimat and IL-ellagic acid proved to be the most sensitive to PEG- Hirudin. The hirudin derivative PEG-Hirudin was. tolerated very well without immuno-allergic side effects. In view of the significantly prolonged anticoagulant efficacy in comparison to non-conjugated r-hirudin, PEG-Hirudin is a promising compound especially for repeated once daily subcutaneous administration.